Impacts of port and locomotive-related air pollution on respiratory symptoms within vulnerable communities in Southern California - Jason G. Su; Vy Vuong; Eahsan Shahriary; John Jacobsen; John Balmes; Meredith Barrett (Environment International, 2025)
The increasing operations of port craft and railway locomotives pose significant environmental and health challenges to vulnerable communities in California, where disadvantaged populations often bear a disproportionate burden of pollution exposure. This study employs digital inhaler sensors to monitor individual respiratory health and quantify the impacts of air pollution from port craft and railway activities on rescue medication use. Combining spatially resolved emissions data with meteorological inputs, we utilized advanced dispersion modeling to estimate pollution levels, focusing on fine particulate matter with an aerodynamic diameter equal to or less than 2.5 µm (PM2.5) and nitrogen dioxide (NO2).Our analysis revealed that a 10-µg m−3 increase in PM2.5 concentrations is associated with a 3.42% rise in daily rescue medication use when accounting for NO2 and PM2.5 jointly. The impacts are particularly pronounced in deprivation-high communities, where the effect of PM2.5 on rescue medication use is 3.8 times greater than in less disadvantaged areas. These findings highlight stark disparities in health outcomes, with marginalized populations facing heightened risks due to their proximity to emission sources and lack of adequate environmental safeguards.While substantial research has addressed air pollution impacts from roadway traffic and industrial activities, studies focusing specifically on port craft and railway emissions remain limited. Our study demonstrates the unique health burdens associated with these underexplored sources of pollution. Furthermore, the use of digital health technologies allows for unprecedented spatiotemporal resolution in tracking exposure and respiratory outcomes, providing a more nuanced understanding of the complex interplay between environmental and health dynamics.These results underscore the urgent need for targeted interventions, including cleaner technologies, stricter emission regulations, and policies aimed at mitigating exposure in vulnerable populations. Addressing these disparities is essential to advancing environmental justice and protecting public health.